PEMUNGUTAN RETRIBUSI PARKIR DI MINIMARKET DITINJAU DARI PERATURAN DAERAH KOTA SURABAYA NOMOR 3 TAHUN 2018 TENTANG PENYELENGGARAAN PERPARKIRAN DI KOTA SURABAYA - Satryadewa, Anggit Daka; Latumahina, Rosalinda Elsina (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Transportation is frequently recognized by many as crucial to the success of a country due to the fact that supports effortless movement of people and goods and contributes to longterm development. The overall objective of transportation is to minimize travel times while stimulating human activity by facilitating connections throughout destinations faster. It must be done to take on transportation wholeheartedly, taking into thought not simply the present situation and conditions but also the environment that surrounds it, including facilities and infrastructure. In addition to an abundance of places to park and expanding vehicular traffic, congestion might get worse as a consequence of a deficiency of supportive infrastructure and facilities. Surabaya is Indonesia’s second-largest city after DKI Jakarta. In recognition of Surabaya’s their image as a metropolis, numerous citizens of other nearby towns decide to make their homes there. Compared with the Central Statistics Agency, Surabaya is projected to be residence approximately 3,157,126 the residents in the year 2020. The astronomical population of the city as well as the immigrant population from outside Surabaya searching jobs or higher learning also contributed to the city’s considerable vehicle occupancy. With so many available parking spots and appropriate ways to get around, the total number of motorized vehicles both two and four wheeled has declined. Based on the Surabaya City Regional Regulation, Law Number 3 of 2018 concerning the Implementation of Parking in the City of Surabaya defines parking as the act of a vehicle putting an end to or standing fixed while the driver dismisses it